Developmental YAPdeltaC determines adult pathology in a model of spinocerebellar ataxia type 1. Issue 1 (December 2017) - Fujita, Kyota; Mao, Ying; Uchida, Shigenori; Chen, Xigui; Shiwaku, Hiroki; Tamura, Takuya; Ito, Hikaru; Watase, Kei; Homma, Hidenori; Tagawa, Kazuhiko; Sudol, Marius; Okazawa, Hitoshi
Abstract YAP and its neuronal isoform YAPdeltaC are implicated in various cellular functions. We found that expression of YAPdeltaC during development, but not adulthood, rescued neurodegeneration phenotypes of mutant ataxin-1 knock-in (Atxn1-KI) mice. YAP/YAPdeltaC interacted with RORα via the second WW domain and served as co-activators of its transcriptional activity. YAP/YAPdeltaC formed a transcriptional complex with RORα oncis -elements of target genes and regulated their expression. Both normal and mutant Atxn1 interacted with YAP/YAPdeltaC, but only mutant Atxn1 depleted YAP/YAPdeltaC from the RORα complex to suppress transcription on short timescales. Over longer periods, mutant Atxn1 also decreased RORα in vivo. Genetic supplementation of YAPdeltaC restored the RORα and YAP/YAPdeltaC levels, recovered YAP/YAPdeltaC in the RORα complex and normalized target gene transcription inAtxn1 -KI mice in vivo. Collectively, our data suggest that functional impairment of YAP/YAPdeltaC by mutant Atxn1 during development determines the adult pathology of SCA1 by suppressing RORα-mediated transcription. Ataxin-1, linked to spinocerebellar ataxia type 1, is known to interact with the orphan nuclear receptor RORα. Here, Fujita and colleagues show that genetic supplementation of RORα-interacting protein YAPdeltaC during early development can rescue the adult pathologies of SCA1 mouse model.